Frameworks and Methods for Evaluating Open Data Platforms Under the Lens of Human-Data Interaction: A Systematic Review - Mendes, Luana B.; Maciel, Cristiano; Berardi, Rita; Nunes, Eunice P. dos Santos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10973, 2025)
Introduction: This systematic review analyzes the literature on Human-Data Interaction (HDI) within the context of open data platforms. Objective: To investigate HDI definitions and challenges, evaluate approaches for assessing platform quality and complex data visualizations, and understand user needs, including those of non-experts. Methodology: A predefined protocol guided a search in digital databases, followed by a rigorous analysis of 25 selected studies. Results: The review reveals a lack of frameworks for evaluating open data platforms. It also highlights significant interaction challenges, such as difficulties in data interpretation and the need for better support for non-specialized users.